Molecular and stable isotope analysis (δ13C, δ2H) of sedimentary n-alkanes in the St. Lawrence Estuary and Gulf, Quebec, Canada: Importance of even numbered n-alkanes in coastal systems. (February 2022) - Imfeld, Anic; Ouellet, Alexandre; Douglas, Peter M.J.; Kos, Gregor; Gélinas, Yves
Highlights: Molecular and compound-specific δ 13 C and δ 2 H analysis used to assess OM sources at 9 sites along an estuary. Large differences in δ 13 C and δ 2 H signatures between odd and even carbon numbered hydrocarbons. Molecular diagnostic ratios misrepresented OM input sources. Ratios often inaccurate as source indicators when more than one OM source present. δ 13 C and δ 2 H signatures of even carbon-numbered n-alkanes essential for discrimination between OM sources. Abstract: Sediments comprise a multitude of inorganic and organic components, with much of the composition of the organics still not fully characterized. Our research targeted n -alkanes, to determine whether compound specific carbon and hydrogen isotope analysis allows for their source identification in coastal sediments. Here, we map the current abundances and sources of straight chain n -alkanes in sediments of the St. Lawrence Estuary and Gulf using molecular (diagnostic ratios) and isotopic fingerprinting (δ 13 C, δ 2 H). n -Alkane abundances (117.11 ± 1.61 to 418.64 ± 70.20 µg/g OC), carbon preference index (CPI; 1.95 ± 0.05 to 5.09 ± 0.10), average chain length (ACL; 28.36 ± 0.02 to 28.97 ± 0.01), proportion of aquatic submerged plants and terrestrial plant inputs (Paq ; 0.295 ± 0.003 to 0.377 ± 0.002), terrigenous aquatic ratio (TAR; 3.43 ± 0.16 to 7.99 ± 0.05), and n -alkane ratio (NAR; 0.169 ± 0.011 to 0.584 ± 0.011) values varied along the terrestrial-marine continuum. Large differences in the concentration weighted average (WA) δ 13 C and δ 2 H for odd and even n -alkanes were found, with WA δ 13 C ranging from −30.9 ± 0.3 to −33.4 ± 0.09 ‰ and −28.8 ± 0.01 to −32.3 ± 0.2 ‰, respectively, and 165.6 ± 3.6 to −200.8 ± 2.4 ‰ and −96.0 ± 2.8 to −158.7 ± 2.1 ‰ for δ 2 H. The diagnostic ratios were shown to misrepresent the input sources of organic matter (OM) and were inaccurate as source indicators when more than one OM source was present. With the addition of compound specific δ 13 C and δ 2 H analysis of n -alkanes, it was determined that the n -alkanes were predominantly derived from natural, rather than anthropogenic sources, with variations being driven by geographic changes in vegetation type and differing ratios of terrestrial and marine OM inputs. Importantly, compound specific isotope analysis of the even numbered n -alkanes would permit identification and tracking of petroleum-derived contaminants. Molecular data alone are ineffective for this, owing to the similarity in CPI values for petroleum-derived contaminants and highly degraded OM which is discharged by the St. Lawrence River into the estuary.